An Elementary Proof of the Existence of a Competitive Equilibrium in a Special Case - Barbolla, Rosa; Corchon, Luis C. (Quarterly Journal of Economics, 1989)
Rosa Barbolla, Luis C. Corchón; An Elementary Proof of the Existence of a Competitive Equilibrium in a Special Case*, The Quarterly Journal of Economics, V